The evaluation of the students in Dumlupinar University Vocational School of Social sciences about levels of financial literacy - Çelikkol, Mediha Mine; Çelikkol, Hakan (Copernican Journal of Finance & Accounting, 2015)
As the world economy grows, financial system as well grows and more people participate. A healthy operation of financial system depends on the condition that all of its parts and components work well together. One of these components is individuals and families. Worldwide, it is estimated that approximately 150 million people join the financial system every year. Control mechanisms are needed for the stability of ever growing financial system and financial literacy comes into prominence in this regard. In this study, we statistically analyzed the factors that affect financial information, behavior and attitudes of students who go to Dumlupınar University Kütahya Vocational School of Social Sciences and then, we determined their level of financial literacy. In order to develop the awareness of financial literacy and to increase the quality of education about this subject, suggestions have been stated in the study.